ANALYSIS AND DESIGN STRUCTURE OF CIDERES HOSPITAL BUILDING - Dede Apip Permana; Fathur Rohman (Journal of Green Science and Technology, 2018)
ABSTRACTA hospital is one of the important elements in the people of nation, especially in the medical sector. Cideres hospital is one of hospital in district Majalengka that has the best services. Healthy is important to make development of quality people sector. Cideres hospital has a target to make Majalengka become a healthy district in Indonesia.As one of citizen needs, healthy is important to make development of quality people sector. Cideres hospital has a target to make Majalengka become a healthy district in Indonesia. After this building constructed, it make the service healthy to the people in Majalengka more increase.In order to create a structure that is safe and meets serviceability limit, in the process of design the building structure must be according to SNI-2847-2013 of reinforced concrete, which are the latest regulations adapted from the latest material technology development refers to the AISC. Besides planning, the loading structure must be according to SNI-1727-2013 and the calculation of earthquake engineering refers to SNI-1726-2012.With the special programs, the completion of structural analysis for various purposes can be performed quickly and accurately, when compared with the structural analysis is done manually including SAP2000 program.Keywords : Analysis and design, SNI codes, SAP2000 Program